Aging and HIV-Related Caregiving in Sub-Saharan Africa: A Social Ecological Approach. (17th October 2017) - Small, Jeon; Aldwin, Carolyn; Kowal, Paul; Chatterji, Somnath
Abstract: Background and Objectives: We reviewed the literature on older adults (OAs) who are caring for persons living with HIV/AIDS in sub-Saharan Africa (SSA), with the goal of adapting models of caregiver stress and coping to include culturally relevant and contextually appropriate factors specific to SSA, drawing on both life course and cultural capital theories. Research Design and Methods: A systematic literature search found 81 articles published between 1975 and 2016 which were reviewed using a narrative approach. Primary sources of articles included electronic databases and relevant WHO websites. Results: The main challenge of caregiving in SSA reflects significant financial constraints, specifically the lack of necessities such as food security, clean water, and access to health care. Caregiving is further complicated in SSA by serial bouts of caring for multiple individuals, including adult children and grandchildren, in the context of high levels of stigma associated with HIV. Factors promoting caregiver resilience included spirituality, bidirectional (reciprocal) caregiving, and collective coping strategies. Discussion and Implications: The creation of a theoretical model of caregiving which focuses more broadly on the sociocultural context of caregiving could lead to new ways of developing interventions in low-resources communities.